Redefiniendo los delitos sexuales facilitados mediante el uso de sustancias psicoactivas = Redefining Drug-Facilitated Sexual Crimes - Agustina, José R. (Política criminal, 2020)
In the Criminal Law and criminological context, chemical submission involves the administration of psychoactive substances to a person, without their consent, for criminal purposes. It is a particularly treacherous way to break the will of the victim in order to commit a crime without their opposition, because the victim is unable to give their consent freely or present resistance to their attacker. In cases of sexual crimes, these behaviors are classified, in the Spanish Criminal Code, as sexual abuse and not as sexual assault. The act of drugging a person without their consent or knowledge is not within the concept of violence according to the law and jurisprudence. On the other hand, it is considered as such in crimes against property. In this article, first, the authors take a contextual, doctrinal and jurisprudential analysis of article 181.2 of the Spanish Criminal Code, where sexual abuse by chemical submission is regulated besides other forms of drug-facilitated sexual assaults; second, they examine some examples in comparative law, with the purpose of studying the differences that exist in this criminal typology, in the context of the nowadays influence of feminist movement in Criminal Law. And third, after a doctrinal analysis on the different issues regarding sexual consent, the authors propose a taxonomy of sex crimes committed without consent and some guidelines to consider before an eventual legal reform.